Excisional treatment in women with cervical adenocarcinoma in situ (AIS): a prospective randomised controlled non-inferiority trial to compare AIS persistence/recurrence after loop electrosurgical excision procedure with cold knife cone biopsy: protocol for a pilot study. Issue 8 (28th August 2017) - Cohen, Paul A; Brand, Alison; Sykes, Peter; Wrede, David C H; McNally, Orla; Eva, Lois; Rao, Archana; Campion, Michael; Stockler, Martin; Powell, Aime; Codde, Jim; Bulsara, Max K; et al.
Abstract : Introduction: Adenocarcinoma in situ (AIS) of the uterine cervix is the precursor to invasive endocervical adenocarcinoma. An excisional biopsy such as a cold knife cone biopsy (CKC) should be performed to exclude invasive adenocarcinoma. Loop electrosurgical excision procedure (LEEP) is an alternative modality to CKC but is controversial in AIS. There is a perception that there is a greater likelihood of incomplete excision of AIS with LEEP because the depth of excised tissue tends to be smaller and the tissue margins may show thermal artefact which can interfere with pathology assessment. In the USA, guidelines recommend that any treatment modality can be used to excise AIS, provided that the specimen remains intact with interpretable margins. However, there are no high-quality studies comparing LEEP with CKC and well-designed prospective studies are needed. If such a study were to show that LEEP was non-inferior to CKC for the outcomes of post-treatment persistence, recurrence and adenocarcinoma, LEEP could be recommended as an appropriate treatment option for AIS in selected patients. This would benefit women because, unlike CKC, LEEP does not require general anaesthesia and may be associated with reduced morbidity. Methods and analysis: The proposed exploratory study is a parallel group trial with an allocation ratio of 2:1 in favour of the intervention (LEEP: CKC). Participants are women aged ≥18 to ≤45 years diagnosed with AIS on cervical screening and/or colposcopically directed biopsy in Australia and New Zealand, who are to receive excisional treatment in a tertiary level centre. Ethics and dissemination: Ethical approval for the study has been granted by the St John of God Healthcare Human Research Ethics Committee (reference number #1137). Results from the study will be presented at conferences and published in a peer-reviewed scientific journal. Registration: ANZCTR registration number ACTRN12617000132347 https://www.anzctr.org.au/Trial/Registration/TrialReview.aspx?id=372173&isReview=true